2021
DOI: 10.4102/sajip.v47i0.1815
|View full text |Cite
|
Sign up to set email alerts
|

Doing gender well: Women’s perceptions on gender equality and career progression in the South African security industry

Abstract: Orientation: Although significant progress has been made globally in gender equality, women still occupy less political influence, fewer leadership positions and yield less control over their careers than most men. Gender inequality is evident in male-dominated work environments such as the security industry.Research purpose: This study reflects on women’s perceptions on gender equality and career progression in the South African security industry.Motivation for the study: In post-democracy South Africa, women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Moreover, it is sometimes addressed from the binary perspective which regards women as the second fiddle, the other sex, and not as equals in terms of political participation. Thus, the ludicrous justification for men's monopoly of prominent political seats of power (Rensburg, 2021).…”
Section: Gender As a Social Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it is sometimes addressed from the binary perspective which regards women as the second fiddle, the other sex, and not as equals in terms of political participation. Thus, the ludicrous justification for men's monopoly of prominent political seats of power (Rensburg, 2021).…”
Section: Gender As a Social Constructmentioning
confidence: 99%
“…Dr. Ngozi Okonjo-Iweala, a Nigerian woman who is currently the Director-General of the World Trade Organization is a noticeable example (BBC News, 2021). Nonetheless, gender inequalities and democratic deficits have remained incessant topical areas under investigation (Rensburg, 2021). This research is therefore focused on the issue of democracy and gender equality in African leadership.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, there is a need for proper coordination of the design and development of tourism training programs at all levels, particularly among MSMEs in Tanzania. Furthermore, it was observed that tourism operators seek a combination of attributes, skills, and experiences with interrelated elements, both informal and structured (Babalola, 2019;van Rensburg, 2021). They further noted that some operators in the industry would prefer conducting in-house and on-job training as opposed to sending their staff to training institutions.…”
Section: Training Needs Assessment In the Tourism Industrymentioning
confidence: 99%
“…The approach aimed to borrow lessons learnt from the previous initiatives to avoid failures in future attempts. The respondents comprised 2 senior tourism officers at MNRT; Executive Secretary for the Tourism Confederation of Tanzania; Chairman and Executive Secretary for the Tanzania Data collection included reviewing the existing tourism and hospitality, and MSMEs documentation, physical and social mapping of MSMEs, in-depth interviews with key informants,Thomann, Ege, & Paustyan, 2022;Van Burg, Cornelissen, Stam, & Jack, 2022). It enables understanding of the social realm or processes through interpretation of the reality of verbal or written recorded respondents' information.…”
mentioning
confidence: 99%
“…Despite these societal challenges, women's participation in the workforce has increased rapidly, and it is estimated that 49.64% of the South African labour force are women (Galal 2022). Jansen van Rensburg (2021) states that in this country fewer women than men occupy influential positions, and that only 32% of women occupy a managerial position. In the past, research on barriers to women's promotion have focused on organisational factors that hinder career progression, such as organisational culture (Fitong Ketchiwou et al 2022;Moalusi & Jones 2019), gender and labour laws, sexual harassment (Pienaar et al 2018;Oosthuizen, Tonelli & Mayer 2019), gender and equality (Coetzee 2017;Naudé 2017), the evolution of the gender struggle (Barclay 2018;Gouws 2019;Lewis 2019), strategies to increase women's representation in certain fields (Mathur-Helm 2018;Matotoka & Odeku 2021), and women-specific experiences impacting their careers (Chetty & Naidoo 2017;Fitong Ketchiwou & Dzansi 2023).…”
Section: Introductionmentioning
confidence: 99%